Analisis Gaya Kepemimpinan Kolaboratif Dalam Penanganan Kebencanaan Pada Kantor Pencarian dan Pertolongan Merauke - Fitriani, Fitriani (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
This study aims to describe the Collaborative Leadership Style in Handling Disasters at the Merauke Search and Rescue Office. The method used is descriptive qualitative, using data obtained from survey results and interviews with 18 informants. The indicators used to describe the collaborative leadership style in accordance with the research framework consist of 8 (eight) indicators, namely understanding the power owned by all parties involved, shared information, democracy, facilitating all parties involved to always brainstorm to obtain mutually agreed decisions, providing time and resources for the benefit of all parties involved, providing opportunities to develop the roles and responsibilities of all parties involved, trying to find solutions to overcome the root of the problem, and offering feedback as soon as possible personally. The results of this study found that the collaborative leadership style carried out by leaders at the Merauke Search and Rescue Office was confirmed from the 8 indicators used, but not maximized in its implementation, it can be seen that there are several emphases given by employees and the community, so it should be a concern for leaders at the Merauke Search and Rescue Office for future improvement. As additional findings, the factors that cause the collaborative leadership style not to be maximized by leaders at the Merauke Search and Rescue Office, First, the external factors of frequent changes in leadership so that the head of the office who is not from Merauke needs time to adapt to employees and the local environment, as well as problems that often occur. The second is the internal factor of the leader which makes him sometimes lack confidence in coordinating with related agencies in a SAR operation.